Epigenom yang Berkembang: Fungsi dan Aplikasinya - Raymond R. Tjandrawinata (MEDICINUS, 2025)
Epigenome is a set of reversible modifications that synergistically regulate gene expression without altering the DNA sequence. The epigenome serves as a functional bridge between the genome and the environment, enabling precise spatiotemporal regulation of gene expression, which is crucial for cellular identity and development of organisms. Unlike the static genome, the epigenome is dynamic and responsive to endogenous and exogenous signals, including developmental, metabolic, environmental stress, and pathological conditions. This paper comprehensively reviews the fundamental mechanisms of epigenetic dynamics, its role in phenotype formation, and its implications in disease etiology and therapeutic innovation. By integrating cutting-edge findings from developmental biology, oncology, neurobiology, and regenerative medicine, the epigenome can be understood as a multidimensional lens for interpreting biological memory, developmental plasticity, and potential molecular engineering.